(untitled) (Research, Society and Development, 2022)
The present study aimed to identify the challenges in promoting research in Brazil from the perspective of the National Council for Scientific and Technological Development - CNPq. From a methodological point of view, this is a descriptive and exploratory study, of a documentary nature, based on the analysis of data from the annual report of accountability of the CNPq management, fiscal year 2016, using Bardin’s content analysis technique. The results found revealed a limitation of budgetary and financial resources (both to honor assumed commitments and to launch innovative actions); insufficient number of civil servants in view of institutional responsibilities and challenges (situation worsened by the growing number of retirements); political and administrative changes. In view of this, it is concluded that there is a gap in financial and human resources aimed at research, which compromises the evolution of science. This fall has been happening gradually and continuously with no prospects of change for growth.